Estudo das concepções de professores da área de ciências naturais sobre as interações entre ciência, tecnologia e sociedade - Miranda, Elisangela Matias (Universidade Federal de São Carlos, 2008)
The current study is intended to investigate the conceptions of a group of Science (elementary) and Biology (high school) teachers who work in public schools (municipal and state) in the city of São Carlos about the Science, Technology and Society (STS) interactions. The relevance of this study lies on the fact that in the present world Science and Technology, with their developments and influences in the human, social, cultural and economical dimensions, have turned to be objects of debates regarding their potentialities, natures and limits, due to many factors, including their impacts on the well-being of society. So, it s considered that the understanding of the nature of science and STS interactions by both the teachers and the students is one of the essential aspects of the scientific literacy, indispensable to a critical and responsible evaluation of the scientific and technological policies. In this study, a qualitative approach has been used to interpret the data collected. The data was obtained by means of the application of, the VOSTS (Views on Science-Technology-Society) questionnaire to a group of elementary and high school Natural Science teachers. They were also submitted to a semi-structured interview with questions based on the VOSTS. The VOSTS questionnaire was applied in an abridged and adapted version. The answers of this version were categorized as realist, plausible and simplistic by Human, Natural and Exact Sciences researchers/professors. The results also show that the participating teachers of this study have some misconceptions about the STS interactions, including these ones: Technology is Science application; Science is a group of information; experiments and observations; Science is a technique for practical problem solving; Science is indefinable; every technological knowledge constitutes itself a single scientific discovery.
Keywords: Professores - formação; Movimento CTS; Ciência e tecnologia aspectos sociais; Inovação curricular; Questionário VOSTS; Entrevista semi-estruturada; CIENCIAS HUMANAS::EDUCACAO